Multiple breath washout and oscillometry after allogenic HSCT: a scoping review - Nicole Sonneveld; Jonathan H. Rayment; Jakob Usemann; Kim G. Nielsen; Paul D. Robinson (European Respiratory Review, 2023)
Pulmonary chronic graft-versus-host disease (cGVHD) is a substantial cause of pulmonary morbidity and mortality post-haematopoietic stem cell transplantation (HSCT). Current spirometry-based monitoring strategies have significant limitations. Understanding the utility of novel peripheral airway function tests – multiple breath washout (MBW) and oscillometry – is critical in efforts to improve detection, facilitate earlier intervention and improve outcomes. In this scoping review, we identified 17 studies investigating MBW or oscillometry, or both, after allogenic HSCT. Despite small study numbers limiting the ability to draw firm conclusions, several themes were evident. Detectable peripheral airway abnormality in MBW occurred in a substantial proportion prior to HSCT. MBW indices post-HSCT were more frequently abnormal than spirometry when reporting group data and among those with extrapulmonary cGVHD and pulmonary cGVHD. Changes in MBW indices over time may be more indicative of pulmonary complications than absolute values at any given time point. Oscillometry indices were often normal at baseline, but more frequently abnormal in those who developed pulmonary cGVHD. Pooling currently available individual participant data across these studies may improve our ability to formally compare their respective sensitivity and specificity at specific time points and assess the trajectory of MBW and oscillometry indices over time.